2003
DOI: 10.3127/ajis.v11i1.145
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Integration and Quality Assurance: a case study of two open source projects

Abstract: A decentralized variant of continuous integration can be defined in terms of two fundamental rules: (1) Developers' access to add contributions to the development version at any time, and (2) developers' obligation to integrate their own contributions properly. Decentralized, continuous integration may adapt well to organizations where developers work relatively independently, as in many open source projects. The approach raises the issue of how these organizations can exercise central control, as attaining th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…Deciding when to integrate changes is also delegated to the developer. This is an advantage when compared to the more plan-driven work assignment process of traditional projects [7]. Breaking down tasks into smaller pieces is also prevalent in open source.…”
Section: Related Workmentioning
confidence: 96%
See 1 more Smart Citation
“…Deciding when to integrate changes is also delegated to the developer. This is an advantage when compared to the more plan-driven work assignment process of traditional projects [7]. Breaking down tasks into smaller pieces is also prevalent in open source.…”
Section: Related Workmentioning
confidence: 96%
“…Holck and Jorgensen [7] studied the use of a decentralized CI process in the open source community (FreeBSD and Mozilla) where developers are often distributed. The authors found that developers working on open source projects are often free to pick any tasks or bugs they want to work on.…”
Section: Related Workmentioning
confidence: 99%
“…The earlier studies [36], [37] interpret CI as distributed development and obligation to integrate one's own contributions. Under this definition no commit size reduction has been observed in 5,122 Ohloh projects [37].…”
Section: Related Workmentioning
confidence: 99%
“…Prior work has also explored the benefits of using continuous integration environments, such as automating the build process [4], only releasing modules after they pass all automated test cases [23], and reducing integration risk by finding errors earlier in the lifecycle [12]. Our work on CiCUTS also shows the benefits of using continuous integration environments to automate key aspects of the testing process.…”
Section: Integrating Sem Tools With Continuous Integration Environmentsmentioning
confidence: 78%
“…In practice, however, these drawbacks are not problematic because agreeing on an intermediate format is straightforward. Moreover, continuous integration environments are used in industrial development [4,12] and support extension for domain-specific needs, such as evaluating the success of results generated by domain-specific extensions.…”
Section: Figure 4 Conceptual Model Of Design Alternativementioning
confidence: 99%